The Values of Versatility: Pharmacists, Plants, and Place in the French (Post)Colonial World - Monnais, Laurence; Tousignant, Noémi (Comparative Studies in Society and History, 2016)
Abstract Colonial pharmacists bio-prospected, acclimatized, chemically screened, and tinkered with plants and their parts, hoping to create products to supply colonial public health care, metropolitan industries, and imperial markets. This article's approach is to examine the trajectories of expertise of two French colonial pharmacists, Franck Guichard and Joseph Kerharo, to illuminate the history of modern medicinal plant research. Both men studied medicinal plants as part of their colonial duties, yet their interests in indigenous therapies exceeded and outlived colonial projects. We take this “overflow” as our point of departure to explore how science transformed medicinal plant values in French colonial and postcolonial contexts. Our focus is on the relationship between value and space—on the processes of conceptual and material (de-/re-)localization through which plant value is calculated, intensified, and distributed. We study and compare these processes in French Indochina and French West Africa where Guichard and Kerharo, respectively, engaged in them most intensively. We show that their engagements with matter, value, knowledge, and mobility defy easy categorizations of medicinal plant science as either extractive or neo-traditionalist. By eschewing simple equations of scientists' motivations with political projects and knowledge-production, we argue that approaching plant medicine through trajectories of expertise opens up grounds for finer analyses of how colonial power and projects, and their legacies, shaped scientific activity.
Keywords: =CL